Evaluación del control interno contable en la Empresa Ote S. A. de la ciudad de Babahoyo en el periodo 2023. - Chávez Velásquez, Johan Jahir (2024)
Internal accounting control is essential for the effective management of any organization. This system includes policies and procedures designed to protect assets, prevent fraud, and maintain accurate records. OTE S.A., a company located in Babahoyo, faces challenges in effectively implementing these systems due to an insufficient understanding of the five fundamental elements of internal control: control environment, risk assessment, control activities, information and communication, and monitoring. The general objective of this study is to examine the internal accounting control at OTE S.A. by analyzing the financial statements for the year 2023. The research falls under the line of Financial Administrative Management, Taxation, Auditing, and Control, with a sub-line in Auditing and Control. The methodology used in this study is based on a systematic and detailed approach to evaluate the effectiveness of the procedures and practices implemented at OTE S.A. It includes the analysis of internal control elements according to the COSO model, the review and verification of inventory accuracy, and the identification and management of accounting and financial risks. This comprehensive approach allows for the identification of weaknesses and areas for improvement, contributing to the continuous training of employees and the strengthening of the company's internal control.